Reclaiming Nostalgia : Longing for Nature in American Literature - Ladino, Jennifer K. (Book collections on Project MUSE., 2012)
Often thought of as the quintessential home or the Eden from which humanity has fallen, the natural world has long been a popular object of nostalgic narratives. This book assesses the ideological effects of this phenomenon by tracing its dominant forms in American literature and culture since the closing of the frontier in 1890. While referencing nostalgia for pastoral communities and for untamed and often violent frontiers, the book also highlights the ways in which nostalgia for nature has served as a mechanism for social change, a model for ethical relationships, and a motivating force for social and environmental justice.